1960
DOI: 10.2105/ajph.50.8.1089
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Diet, and Calcium Metabolism in Dental Health

Abstract: It is recognized that there is an intricate, close connection between diet, nutrition, and dental health. Yet there are still gaps in knowledge. The relation of nutrition and diet to dental caries and periodontal disease are considered in the following paper, and the author considers what we know and what still remains to be discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1961
1961
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…An additive protection of the teeth with water-borne fluoride and dietary phosphate supplement has been reported by Mühlemann et al [1961] and van Reen et al [1962]. On the other hand, Johansen [1960], Navia and H arris [1969] and N izel et al [1970] obtained a similar effect with dietary phosphate and fluoride ad ditives. In a later study of the Swiss group [Mühlemann and König, 1964] a combination of Na.HPO., and NaF was found no more effective than NaF alone.…”
Section: Discussionmentioning
confidence: 61%
“…An additive protection of the teeth with water-borne fluoride and dietary phosphate supplement has been reported by Mühlemann et al [1961] and van Reen et al [1962]. On the other hand, Johansen [1960], Navia and H arris [1969] and N izel et al [1970] obtained a similar effect with dietary phosphate and fluoride ad ditives. In a later study of the Swiss group [Mühlemann and König, 1964] a combination of Na.HPO., and NaF was found no more effective than NaF alone.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, the pulp is a live tissue composed of different glycosaminoglycans with some collagenous fibers, nerves, blood supply, and lymphatic systems . The chemical composition of teeth can also be influenced by numerous factors including diet/nutrition, age, dental diseases, type of teeth (deciduous or permanent), and genetic factors …”
Section: Introductionmentioning
confidence: 99%
“…[12] The chemical composition of teeth can also be influenced by numerous factors including diet/nutrition, age, dental diseases, type of teeth (deciduous or permanent), and genetic factors. [13,14] Dental hypomineralization is a relatively common anomaly. Typically, it occurs within the enamel and presents with white, yellow, or brown opacities with altered translucency.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction is mainly the result of a local effect on the tooth surface, and involves a retardation of the development of caries rather than a prevention of the initiation of caries. Johansen (1960) observed that when 2% CaHP04 and fluoride were fed together, caries development was less than when either was fed alone. Muhlemann and coworkers (1961a) noted a similar response when 0.4% sodium acid phosphate and 100 ppm Fwere added to the diet of rats.…”
Section: Phosphatementioning
confidence: 96%